2020
DOI: 10.1016/j.mjafi.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2: Camazotz's Curse

Abstract: The world is currently face to face with a pandemic which is spreading rapidly across the globe caused by SARS-CoV-2, a strain of Coronaviruses (CoVs) belonging to subgenus Sarbecovirus of genus Betacoronavirus. World Health Organisation (WHO) on 11 Feb 20 named this disease caused by SARS-CoV-2 as Covid-19. This pandemic is spreading rapidly and more than 20,00,000 cases have occurred globally. The human Coronaviruses discovered in 1960s were considered potentially harmless endemic viruses with seasonal distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 23 publications
3
55
0
8
Order By: Relevance
“…4 Comparative genome analyses of SARS-CoV-2 with Coronaviruses from bats and pangolins show 96.2% and 91% similarity, respectively. 5 These studies suggest a high possibility of the virus to have originated or come through bats and pangolins.…”
Section: The Novel Sars-cov-2mentioning
confidence: 99%
“…4 Comparative genome analyses of SARS-CoV-2 with Coronaviruses from bats and pangolins show 96.2% and 91% similarity, respectively. 5 These studies suggest a high possibility of the virus to have originated or come through bats and pangolins.…”
Section: The Novel Sars-cov-2mentioning
confidence: 99%
“…Proteins from SARS and SARS-CoV-2 were treated as homologous: identity value > 65%, query coverage, >95% [160]. SARS-CoV-2 has been found to be more distant in relation to SARS-CoV (79%) and MERS-CoV (50%) [161]. Anand et al found that all sequences showed ~99.98% similarity in the nucleotide sequences, implying a relationship between the currently circulating viruses and suggesting a recent shift to humans [161].…”
Section: Comparison Of Sars-cov-2 Sequences With Other Coronavirusesmentioning
confidence: 99%
“…Other studies have shown that the homology with a coronavirus strain isolated from pangolin was 99%, suggesting that SARS-CoV-2 might have originated from bat and pangolin might have served as the intermediate host between bat and human [165]. The genetic analysis of the currently circulating strains of the pandemic have shown 99.98-100% similarity in their genomes, implying a recent shift to humans [161]. Description of the epitopes distribution over the viral population might provide valuable information driving future researches aimed at setting efficient prophylactic strategies and/or the design of tool capable of differential diagnosis on the basis of serological tests.…”
Section: Comparison Of Sars-cov-2 Sequences With Other Coronavirusesmentioning
confidence: 99%
“…Even prior to the current pandemic, some of the earlier known coronaviruses have been transmitted from civet cats and dromedary camels although their spread has not been as prevalent. These viruses cause a range of diseases from mild cold to infections with high mortality such as Severe Acute Respiratory Syndrome (SARS) or Middle East Respiratory Syndrome (MERS) [6,7].…”
Section: Origin and Spread Of The Pandemicmentioning
confidence: 99%